LIPCPM: A Novel Model for Anti-Sloshing and Stable Bipedal Robot Locomotion - Hosun Kang; Jaehyung Park; Dongyoung Lee; Jungmin Lee; Inho Lee (IEEE Access)
In this paper, we propose a novel model, the Linear Inverted Pendulum with Cart-Plate Model (LIPCPM), which combines the Linear Inverted Pendulum Model (LIPM) with a mass-spring-damper model to simultaneously control both the legged robot and the sloshing phenomenon. A legged robot transporting liquid-filled container exhibits significant nonlinearities due to the sloshing dynamics of fluid movement within a confined container and the dynamics of legged robot itself. Therefore, controlling the legged robot and sloshing phenomenon together will bring challenges. Since the robot receives the reaction forces by the sloshing dynamics, simply implementing LIPM on the robot carrying a liquid container would not be enough. So, we analyzed how the reaction forces affect the robot with actual experiments and tabulated the system parameters that can be integrated with the LIPM. The experimental results show that the reaction forces by the sloshing dynamics are similar to those of a second-order response. The proposed model could be utilized with the Model Predictive Control (MPC), and predicted future states of the robot and liquid were controlled as we desired. Finally, we demonstrate the effectiveness of the proposed system in simulation with experimental-based system parameters for reliability. According to the results, the Root Mean Square Error (RMSE) of sloshing phenomenon under various conditions was decreased by approximately 70 %.